Challenges in Understanding Compliance Behaviour of Taxpayers in Malaysia - Ern, Chen Loo; Evans, Chris; McKerchar, Margaret (Asian Journal of Business and Accounting, 2010)
Since the implementation of self assessment in Malaysia almost a decade ago, taxpayers’ compliance behaviour has attracted considerable attention. Tax compliance research in Malaysia has predominantly been in the context of income tax and personal taxpayers, and has been conducted using survey methods and experimental approaches. Access to taxpayers’ data is rarely made available to academic researchers by the Inland Revenue Board of Malaysia (IRB), thus studies have tended to rely on self-reported behaviour and convenience sampling which have limited the extent to which findings can be generalised. Further, most studies have considered only a limited range of variables that may or may not influence compliance behaviour which is widely recognised as being a complex phenomenon. Based on studies to date, it appears that Malaysian taxpayers have high ethics and that individuals’ tax knowledge is a key influence on their compliance behaviour. Scope exists for further research using a range of methodologies, studies that are more comprehensive and longitudinal, and using a wider range of taxes, taxpayers, and compliance obligations.